Towards the Quadruple Aim in permanent supportive housing: A mixed methods study of workplace mental health among service providers. (22nd September 2022) - Kerman, Nick; Goodwin, Jordan M.; Tiderington, Emmy; Ecker, John; Stergiopoulos, Vicky; Kidd, Sean A.
Abstract: The Quadruple Aim is a health policy framework with the objective of concurrently improving population health, enhancing the service experience, reducing costs and improving the work‐life of service providers. Permanent supportive housing (PSH) is a best practice approach for stably housing people experiencing homelessness who have diverse support needs. Despite the intervention's strong evidence base, little is known about the work‐life of PSH providers. This study explored the mental health and work challenges experienced by PSH providers in Canada. Using an explanatory sequential, equally weighted, mixed methods design, 130 PSH providers were surveyed, followed by semi‐structured interviews with 18 providers. Quantitative findings showed that 23.1% of PSH providers had high psychological distress. Participants who were younger, spent all or almost all of their time in direct contact with service users and had less social support from coworkers were significantly more likely to have high psychological distress. Three themes were identified from the qualitative analysis that showed how PSH providers experience psychological distress from work‐related challenges: (a) Sisyphean Endeavours: 'You Do What You Can', (b) Occupationally Unsupported: 'Everyone Is Stuck in Their Zone' and (c) Wear and Tear of 'Continuous Exposure to Crisis and Chaos'. The themes interacted with systemic ( Sisyphean Endeavours ) and organisational issues ( Occupationally Unsupported ), intensifying the emotional burden of day‐to‐day work, which involved frequent crises and uncertainty ( Wear and Tear of 'Continuous Exposure to Crisis and Chaos' ). The findings underscore how these challenges threaten providers' wellness at work and have implications for the care provided to service users. Accordingly, the Quadruple Aim is a potentially useful and applicable framework for measuring the performance of PSH programs, which warrants further consideration in research and policy.